Development of a loop-mediated isothermal amplification (LAMP) assay for molecular identification of Trueperella abortisuis isolated from pigs. (April 2022) - Ahmed, Marwa F.E.; Alssahen, Mazen; Lämmler, Christoph; Foster, Geoffrey; Kreitlow, Antonia; Hennig-Pauka, Isabel; Plötz, Madeleine; Abdulmawjood, Amir
Abstract: The first description of Trueperella ( T. ) abortisuis was presented in Japan in 2009 by Azuma and colleagues. In the current study, eight T. abortisuis strains were identified by a newly developed loop-mediated isothermal amplification (LAMP) assay based on the glyceraldehyde 3-phosphate dehydrogenase (GAPDH) encoding gene gap . Two T. abortisuis strains were obtained from prepuce of a seven-month-old boar and pooled foetal stomach contents in the United Kingdom, while the other six T. abortisuis strains were recovered from aborted foetal material of six pigs from a single farm in Germany. The developed LAMP assay showed an analytical sensitivity of 22 pg μL -1 T. abortisuis DNA. T. abortisuis DSM 19515 T and field strain T. abortisuis P504054/19/1 were directly detectable in artificially contaminated vaginal swabs up to concentrations of 980 CFU and 770 CFU per swab, respectively. There was no cross reactivity with control strains representing six species of genus Trueperella and six species of the closely related genus Arcanobacterium and Schaalia ( Actinomyces ) hyovaginalis . Further field research is required to determine the usefulness of the designed LAMP assay for identifying T. abortisuis isolated from pigs of various origins and from test samples directly obtained at farm level. Highlights: The gap -specific LAMP assay could successfully identify the species-specific gene gap of T. abortisuis isolates. The LAMP assay shows high sensitivity and specificity. DNA was detected in unprocessed vaginal swabs spiked with T. abortisuis.